Case History of Severe Toxicoallergic Dermatitis in Patient with Acute Leukemia - Igor Y. Gadaev (Journal of Global Pharma Technology, 2020)
Adverse drug reactions are a serious problem in practical healthcare since they can have a significant impact on the patients’ quality of life while the global prevalence of morbidity and mortality caused by drug after-effects is increasing every year. Among the most common adverse drug reactions are skin reactions. They have described a case history of severe furosemide-induced toxicoallergic dermatitis in a 62-year-old man with acute myeloid leukemia taking saluretic due to comorbid cardiac pathology. Furosemide was withdrawn due to of severe toxicoallergic dermatitis onset while the glucocorticosteroids therapy with a 40 mg qd dose of prednisolone was prescribed. Secondary to furosemide withdrawal and due to glucocorticosteroid therapy, the following amelioration was registered: there were no new lesions, bullae and anabrosis disappeared, edema decreased and the patient’s general state of health improved. The described case of severe furosemide-induced toxicoallergic hemorrhagic vasculitis is associated not only with the direct allergenic action of the drug being the sensitization reaction trigger, but is also associated with the aberrant immunoreactive status of a particular patient due to his hematologic malignancies (acute myeloid leukemia). Such severe toxicoallergic reactions are rare enough, but it is extremely important to draw the clinicians’ attention to this problem, since these are the timely diagnosis of mentioned conditions, the identification and elimination of the trigger drug, timely and adequate treatment that guarantee a favorable prognosis for patients. That is why clinicians should not only aim for the verification and treatment of the underlying disease, but also consider the patient's comorbid conditions. Keywords: Drug-induced dermatitis, furosemide-induced severe toxicoallergic dermatitis, Delayed-onset allergy, Toxicoallergic dermatitis in acute leukemia.